Procedural Justice and Managers' In-Role and Extra-Role Behavior: The Case of the Multinational - Kim, W. Chan; Mauborgne, Renée A. (Management Science, 1996)
Existing procedural justice studies to date offer only pieces of the picture on how procedural justice judgments affect behavior. Besides, these studies have been conducted primarily in the legal context. This paper develops a comprehensive picture of how procedural justice affects managers' in-role and extra-role behavior in the business context. It does so by examining the direct and indirect effects of procedural justice judgments on the in-role and extra-role behavior of multinationals' subsidiary top management in the context of the global resource allocation decision process. Especially, this paper advances and tests a theory which predicts that the attitude of commitment to support decisions provides a bridge between procedural justice and extra-role behavior. Based on an analysis of 119 subsidiary top managers, we offer evidence in support of this theory. Besides its contribution to the procedural justice literature, our study also sheds light on one of the most pressing issues outstanding in the field of international management: how multinationals can motivate subsidiary top managers to implement their global resource allocation decisions. The results suggest that the exercise of procedural justice inspires managers to go beyond the call of duty and engage in innovative actions, spontaneous cooperation, and creative behavior on behalf of the organization in their execution of decisions.